2022
DOI: 10.3389/fpsyg.2022.880894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicopter Parenting on Tutoring Engagement and Continued Attendance at Cram Schools

Abstract: Attending cram school has long been a trend in ethnic Chinese culture areas, including Taiwan. Despite the fact that school reform policies have been implemented in Taiwan, cram schools have continued to prosper. Therefore, in this educational culture, how to achieve a good educational effect is also a topic worthy of discussion. However, whether students really engage in those tutoring programs provided by cram schools has seldom been studied. To address this gap, this study explored how parents’ hovering att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Children tend to hide their emotions or have variable emotions, intimacy is relatively difficult to establish, and the parent–child bonding is in an unhealthy state of development ( Hollenstein and Lewis, 2006 ; Duncan et al, 2009 ; Tao et al, 2020 ). The “helicopter parenting” of a collectivist society produces “good children who know what they are doing” and “subordinates who do not think for themselves but follow orders ( Ho et al, 2022 ; Hwang et al, 2023 ). “Helicopter parents” interfere and manipulate their children’s thoughts and behavior always, and help them decide everything.…”
Section: Discussionmentioning
confidence: 99%
“…Children tend to hide their emotions or have variable emotions, intimacy is relatively difficult to establish, and the parent–child bonding is in an unhealthy state of development ( Hollenstein and Lewis, 2006 ; Duncan et al, 2009 ; Tao et al, 2020 ). The “helicopter parenting” of a collectivist society produces “good children who know what they are doing” and “subordinates who do not think for themselves but follow orders ( Ho et al, 2022 ; Hwang et al, 2023 ). “Helicopter parents” interfere and manipulate their children’s thoughts and behavior always, and help them decide everything.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the shared cultural values, helicopter parenting behaviors in Korea and China have some similarities. They are characterized by excessive emphasis on academic achievement, in addition to commonly observed helicopter parenting behaviors, such as monitoring children's social activities, making decisions for them, and providing excessive care (Kwon et al, 2017;Ho et al, 2022). For example, Leung and Shek (2019) found that helicopter parents tended to over-emphasize academic performance in China because it can be considered the only indicator of future success.…”
Section: Cultural Similarities and Differences In Helicopter Parentin...mentioning
confidence: 99%